2015
DOI: 10.1097/01.omx.0000462966.49834.d6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet-rich fibrin on alveolar bone height after removal of impacted lower third molar

Abstract: Objectives This study aimed to assess the effect of platelet-rich fibrin (PRF) on both bone and supporting tissue healing after surgical removal of impacted lower third molar using the digital panoramic bitewing technique.Patients and methods Twenty patients complaining of a bilaterally impacted lower third molar were included in the study. The surgical treatment plan was removal of bilaterally impacted lower third molar during the same visit under local anesthesia. For the study group, represented by the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…21,22 were related to extraction of teeth prior to rehabilitation with dental implants, the results of the studies showed no significant differences for bone filling both clinically and radiographically (P> 0.9; P< 0.5), respectively. 8 studies [20][21][22][23][24]27,[36][37][38][39][40] were related to tooth extraction due to endodontic failure and coronary fracture, where the results showed that the loss of alveolar ridge width in the test group was less than in the control group (-0.97mm, -1.92mm), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 were related to extraction of teeth prior to rehabilitation with dental implants, the results of the studies showed no significant differences for bone filling both clinically and radiographically (P> 0.9; P< 0.5), respectively. 8 studies [20][21][22][23][24]27,[36][37][38][39][40] were related to tooth extraction due to endodontic failure and coronary fracture, where the results showed that the loss of alveolar ridge width in the test group was less than in the control group (-0.97mm, -1.92mm), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…26 Fontes & cols, 28 reported in their study conducted in 2020 that tissue mineralization using PRF may have some potential to increase it, however, no significant differences were evidenced between the test and control group (P> 0.05). 27 Gasparro et al, 29 in 2020 reported that PRF shows better results in clinical insertion loss (CAL) gain and probing depth reduction, but there was no significant difference, PRF (0.47±0.41 mm) compared to the control group (0.60±0.46 mm). 28 Guzmán & cols, 30 in their 2017 study, showed that there was a difference in bone tissue healing at 60 days of control (p< 0.015).…”
Section: Discussionmentioning
confidence: 96%